GAE-YOLO: a lightweight multimodal detection framework for tomato smart agriculture with edge computing - Liu, Xiaoke; Teng, Wenjie; Yu, Haoran; Yao, Zhuoyi; Wang, Chengzhen; Peng, Yuzhong; Han, Xiaoqing; Liu, Jianming (Frontiers in Plant Science, 2025)
IntroductionThe advancement of smart agriculture has witnessed increasing applications of computer vision in crop monitoring and management. However, existing approaches remain challenged by high computational complexity, limited real-time capability, and poor multi-task coordination in tomato cultivation scenarios.MethodsTo address these limitations, an intelligent tomato management system is proposed based on the Ghost-based Adaptive Efficient You Only Look Once (GAE-YOLO) algorithm. The lightweight architecture of the GAE-YOLO framework is achieved through the replacement of standard convolutional layers with Ghost Convolution (GhostConv) modules, while detection accuracy is significantly improved by the integration of both AReLU activation functions and Effective Intersection over Union (E-IoU) loss optimization. The system, implemented on a Jetson TX2 embedded platform, also incorporates ZED stereo vision for 3D localization and a PyQt6-based visualization platform.ResultsWhen implemented on Jetson TX2, the system achieving 93.5% mean Average Precision at 50% intersection over union (mAP@50) at 10.2 frames per second (FPS), which can be optimized to 27 FPS by employing TensorRT acceleration and 720p resolution for scenarios demanding higher throughput. Furthermore, it establishes standardized assessment systems for tomato maturity and yield prediction, and offers integrated modules for disease diagnosis and agricultural large language model consultation.DiscussionThis work establishes a new paradigm for edge computing in agriculture while providing critical technical support for smart farming development.